Orofacial symptoms and oral health-related quality of life in juvenile idiopathic arthritis: a two-year prospective observational study - Hanna Rahimi; Marinka Twilt; Troels Herlin; Lynn Spiegel; Thomas Klit Pedersen; Annelise Küseler; Peter Stoustrup (BMC, 2018)
Abstract Background Little is known about the chronicity of orofacial symptoms and how this influences the oral health-related quality of life in juvenile idiopathic arthritis (JIA). Therefore, our objectives were to study the long-term changes in self-reported orofacial symptoms, and to define the impact of orofacial symptoms on oral health-related quality of life in JIA. Methods At baseline (T0), 157 consecutive JIA patients ≤20 years completed a patient pain questionnaire that incorporates domains related to the orofacial area. At the 2 year follow-up (T1), 113 patients completed the same questionnaire (response rate 72%) in addition to the Child Perception's Questionnaire; a validated 31-item questionnaire addressing oral health-related quality of life. Results At T0, 53% (60/113) of patients reported the presence of orofacial pain, and 36% (41/113) of patients reported compromised orofacial function. At T1, 77% (46/60) of patients with pain at T0 reported persistent pain, and 66% (27/41) of patients with functional disability at T0 reported persistent disability. Patients with orofacial symptoms reported a significantly greater prevalence of negative impact of orofacial conditions on general quality of life and within the domains of emotional and social well-being compared to asymptomatic patients. Conclusion Self-reported orofacial pain and functional disability were common findings in a cohort of JIA patients followed over 2 years. These symptoms seem to persist over time in most patients, and have a significant negative impact on oral health-related quality of life.